Kalman Filter Estimation of the Unrecorded Economy in Macedonia - Branimir Jovanovic (National Bank of the Republic of Macedonia, 2015)
This paper estimates the unrecorded economic activity and employment in Macedonia during 1998-2013. We model the unrecorded economic activity as an unobserved process that depends on tax "burden", business regulations and quality of governance, and affects cash in circulation, foreign currency in circulation and energy consumption. We then estimate it, using the Kalman filter. After we estimate the unrecorded economic activity in this way, we calculate the unrecorded employment using a wide range of values for the employment/economic activity ratio. Finally, after we estimate the unrecorded employment, we will be able to calculate the true rate of unemployment in Macedonia. The findings suggest that unrecorded economic activity in Macedonia has declined sizeably, from 34 percent of official GDP in the late 1990's, to 10 percent in 2010's. Unrecorded employment has declined over this period, too, from 160-200,000 in late 1990's to 70-90,000 currently. Accordingly, the true rate of unemployment was likely to be around 20-22% in 2013, which is some 7-8 percentage points below the official one.
Keywords: E26; J46; 330; unrecorded economy; unrecorded employment; Kalman filter; Macedonia